Empirical Understanding of Social Protection Programmes in Southwest Coastal Areas of Bangladesh: A Postmodern Perspective - Rahman, Md Mostafizur (European Journal of Social Science Education and Research, 2021)
Social protection programmes in Bangladesh aimed at reducing the vulnerability of the poor has become exceptionally challenging because of high exposure to weak institutional governance, and frequent natural disasters. As a matter of fact, both the coverage and the types of social protection programmes have been expanded to support the extremely poor households in Bangladesh over the last decade. However, the boundaries between ‘protection approach’ associated with risk reduction and ‘promotion approach’ regarded as the pathways to raise incomes and employment opportunities of the poor have remained understated in policy discourse. This paper addresses how an Interpretivist methodology can be used in exploring the current complexities of social protection programmes in extremely poor households with reference to disaster-affected areas in southwest coastal Bangladesh, giving a particular attention to the interpretation of the beneficiaries as well as service providers. This paper employs an interpretative framework for collecting qualitative data because of its ability to make sense of the complex situations of social protection programmes by generating multi-contextual information provided by the beneficiaries of social protection programmes. During the initial fieldwork of the research, the research participants pointed out that there exist strong prevalence and dominance of local politics considered as ‘underlying issues’ in the delivering process of social protection programmes, which is further associated with power-relation between the rich and poor class of the society. However, the current policy discourses of social protection programmes have overlooked those highly pertinent phenomena both in local and national context. This paper argues that the aspects of availability, accessibility and utilisation of social protection programmes is not straightforward as each aspect is further associated with social relations and complex social understanding. An interpretive methodology along with illustrative data collection and analysis techniques can become effective to explore those complex societal understanding related with social protection programmes. Finally, within the adopted interpretive framework, the integrated view related with availability, accessibility and utilisation aspects of social protection programmes need to be addressed while creating a sense of meaning and understanding of overall situation of social protection programmes.